Personal Hygiene Berhubungan dengan Keputihan pada Remaja Putri di SMA Negeri 1 Pajangan Yogyakarta - Septia Nanda Sari; Dwi Susanti (Wiraraja Medika : Jurnal Kesehatan, 2026)
Vaginal discharge is one of the most common reproductive health issues among adolescent girls. Abnormal vaginal discharge can cause discomfort and even serious infection risks if not properly managed. One of the contributing factors is poor personal hygiene practices, such as not changing sanitary pads regularly, wearing underwear that does not absorb sweat, and failing to maintain proper hygiene in the genital area. The aim of this research is to determine the relationship between personal hygiene behavior and vaginal discharge issues among adolescent girls at State Senior High School 1 Pajangan, Yogyakarta. This study used a quantitative method with a cross-sectional approach. Data collection was conducted at SMA Negeri 1 Pajangan Yogyakarta in June 2025. The sample consisted of 85 female students in grades X and XI, selected using stratified random sampling. The criteria for respondents were female students in grades X and XI who were willing to be respondents and signed an informed consent form. Data were collected using two types of questionnaires, namely a personal hygiene behavior questionnaire and a vaginal discharge questionnaire. Data were analyzed using Somers' d statistical test. The study results showed that most respondents had high personal hygiene behavior (55,3%) and experienced mild vaginal discharge (52,9%). The Somers’d test yielded a p-value of 0.001 (<0.05). There is a significant asseciation between personal hygiene behavior and vaginal discharge issues among adolescent girls.